Some Aspects of Research Into the Social Skills of Visually Impaired Youth - Raudeliūnaitė, Rita (Acta Paedagogica Vilnensia, 2005)
The article provides the results of the research into social skills of the visually impaired youth. Greatest attention is given to the disclosure of the young people’s approach towards the development of social skills at school. Also those social skills are emphasized which are least developed by students when they graduate from the secondary school. In order to disclose the level of social skills acquired at school by the visually impaired young people, key attention has been concentrated on the skills in the area of self-evaluation, communication, co-operation, resolving of problems and conflicts, stress-overcoming, emotion management, understanding of other people’s emotions. Said skills have a strong impact on the person’s capacity to create and maintain positive mutual relationships, to be on friendly terms with other people, to develop relations of partnership and they are helpful in order to have a better orientation in different situations and environments. Results obtained in the course of the research do not define the approach of all visually impaired young people to the acquisition of social skills at school, however, they allow to state certain tendencies which demonstrate the urgency of this problem. The data of the research demonstrated that although more than half of the respondents had positively evaluated acquisition of skills while at school in the area of communication, co-operation, problem-solution, overcoming of stress, however, about half of the questioned indicated that they found it difficult to establish contacts with others, to find friends, to ask for assistance. Besides, only the sixth part of the respondents found it not difficult to get to know emotions of other people. Approximately half of the respondents had not had a positive approach to the level of skills acquired at school in the area of emotion-management, knowledge of other people’s emotions, conflict-resolution and resistance to other people’s pressures either. Said skills significantly impact on the capacity of the person to maintain balance between personal and social aspirations, help to maintain effective mutual relationships and to control oneself in difficult situations. Certainly, manifestation of social skills is not a consequence which forms itself on its own, for that purpose it is necessary to form favourable educational conditions which would help develop possibilities of the person’s social experience, foster better self-knowledge and self-understanding, acquisition of valuable experience in the area of communication and co-operation.